Effect of angiotensin I-converting enzyme (ACE) inhibition and nitric oxide (NO) production of 6, 6′-bieckol, a marine algal polyphenol and its anti-hypertensive effect in spontaneously hypertensive rats. (July 2017) - Ko, Seok-Chun; Kang, Min Cheol; Kang, Nalae; Kim, Hyun-Soo; Lee, Seung-Hong; Ahn, Ginnae; Jung, Won-Kyo; Jeon, You-Jin
Graphical abstract: Highlights: 6, 6′-Bieckol exhibited potential ACE inhibition and NO production. 6, 6′-Bieckol activates eNOS by activating Akt pathway. 6, 6′-Bieckol inhibits ACE activation by the Pi interaction with ACE. Oral administration of 6, 6′-bieckol lower blood pressure in SHR. Abstract: In the present study, the effects of 6, 6′-bieckol isolated from Ecklonia cava on angiotensin I-converting enzyme (ACE) inhibition and nitric oxide (NO) production, and the inhibitor's binding modes using the crystal structure of ACE were examined. The effects of 6, 6′-bieckol on systolic blood pressure (SBP) after meals were also investigated. We predicted the 3D structure of ACE and used a docking algorithm to understand the binding between ACE and 6, 6′-bieckol. The molecular docking study revealed that ACE inhibitory activity of 6, 6′-bieckol was mainly attributed to the hydrogen bond interactions (Lys454, His353, Glu162, Glu376, Glu384 and Glu411) and Pi interactions (Lys511 and His513) between ACE and 6, 6′-bieckol. 6, 6′-bieckol significantly increased the production of nitric oxide (NO) and by phosphorylating endothelial nitric oxide synthase (eNOS) in human endothelial cells. Furthermore, antihypertensive effect in spontaneously hypertensive rats (SHRs) also revealed that oral administration of the compound can down-regulate (28.6 mmHg in 6 h) systolic blood pressure (SBP).